Implementation of Digital Spatial-Based Educational Model Innovation in High Schools in the Islands of North Sulawesi Province - Herman Meiky Koessoy; Joulanda A M Rawis; Orbanus Naharia; Mozes M. Wullur (International Journal of Information Technology and Education, 2025)
The gap in education quality and access in island and border regions remains a structural problem in the Indonesian education system. Fragmented geographical conditions, limited infrastructure, and uneven distribution of educational resources demand innovative, contextual and adaptive educational models. This study aims to analyze the implementation of innovative spatial digital education models in Senior High Schools (SMA) in the Sangihe Islands Regency, North Sulawesi Province. Specifically, this study examines the readiness of spatial digital technology infrastructure, the implementation of spatial digital technology-based curriculum, the impact of these innovations on student achievement, local government policy support, and factors influencing their implementation. This study uses a qualitative descriptive approach with a prospective case study design. Data were collected through field observations, in-depth interviews, and documentation studies involving policy stakeholders, principals, teachers, and students. Data analysis was conducted using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of spatial digital education in Sangihe Islands Senior High Schools is still in its early stages, characterized by limited network infrastructure, suboptimal utilization of geospatial applications in learning, and variations in teachers' digital literacy competencies. However, regional policy support and human resource potential indicate significant opportunities for the development of sustainable spatial digital education models. This research confirms that integrating digital and spatial approaches can be an alternative strategy for improving access, relevance, and quality of education in archipelagic and border regions